A methodology for determining the methane flow space in abandoned mine gobs and its application in methane drainage. (1st September 2018) - Feng, Guorui; Zhang, Ao; Hu, Shengyong; Cheng, Jianwei; Miu, Xuyang; Hao, Guocai; Han, Dandan; Guan, Shuwen; Zhao, Guozhen
Abstract: Abandoned mine gobs contain a considerable amount of methane. Determining the methane flow space scientifically will directly affect the methane extraction of abandoned mine gobs. In this paper, a method is proposed to determine the gob methane flow space, based on the geological conditions of the Yongan abandoned mine in China. Physical simulation experiments were firstly conducted to simulate the abandoned gob formations. Subsequently, gas injection experiments were adopted to study the methane concentration distribution in the simulated gobs. The methane flow space was then determined based on the obtained methane concentration distribution. The results demonstrate that the methane flow space of abandoned mine gobs can be divided into four zones from the bottom to the top: methane high-concentration zone (MHZ), methane transition zone (MTZ), methane enrichment zone (MEZ) and methane no-stream zone (MNZ). The boundaries of these zones consistently exhibit a 'V' shape. The methane concentration in the MHZ is evidently higher than those in the MTZ and MEZ. The MTZ restrains the methane flow and causes a sharp decrease of the methane concentration in it. The methane in the MEZ is enriched as one shifts upwards and its concentration increases exponentially. Methane is absent in the MNZ. Based on these results, two surface vertical boreholes of the Yongan abandoned mine were selected to set their bottoms into the MEZ and MHZ, respectively. The field testing results demonstrate that the methane drainage flow rate at the bottom of the borehole located in the MHZ can increase by 1.5 times than that in the MEZ.